INISIASI APOTEKER KELUARGA UNGGULAN DENGAN PENDEKATAN REAL TEACHING ACTION DI DESA SENDANG - Khoiry, Qisty Aulia; Ulfa, Fathya; Wulandari, Wening; Syafira, Muthia; Sasongko, Heru (Jurnal BALIRESO, 2019)
Rational drug use is a very warm discussion in the health care system in Indonesia. This is possiblebecause of reports of the occurrence of errors in the selection and use of drugs freely by thecommunity without based on adequate knowledge, causing undesirable side effects. Real TeachingAction (RTA) is an effort to improve people's knowledge through short learning activities aboutdrug information. The information conveyed among others is about the classification of drugs, thesteps to use the drug